Use of guidelines improves the neurological outcome in glutaric aciduria type I - Heringer-Seifert, Jana; Boy, Nikolas; Ensenauer, Regina; Assmann, Birgit; Zschocke, Johannes; Harting, Inga; Lücke, Thomas; Maier, Esther M.; Mühlhausen, Chris; Haege, Gisela; Hoffmann, Georg F.; Burgard, Peter; et al. (Annals of neurology, 2010)
Objective: To evaluate the effect of treatment according to current evidence-based recommendations on the neurological outcome of patients with glutaric aciduria type I (GA-I). Methods: Fifty-two patients identified by newborn screening (NBS) in Germany from 1999 to 2009 were followed prospectively. Neurological outcome was assessed by the occurrence of an acute encephalopathic crisis and the severity of a movement disorder (MD) with predominant dystonia superimposing on axial hypotonia. Outcome was evaluated in relation to therapy and therapy-independent parameters. Results: Outcome was best in GA-I patients who were treated in full accordance with treatment recommendations (n=37; 5% MD). Deviations from recommended basic metabolic treatment (low-lysine diet, carnitine) resulted in an intermediate outcome (n=9; 44% MD), whereas disregard of emergency treatment recommendations was associated with a poor outcome (n=6; 100% MD). Treatment regimens deviating from recommendations significantly increased the risk for MD (odds ratio [OR], 35; 95% confidence interval [CI], 5.88-208.39) and acute encephalopathic crises (OR, 51.32; 95% CI, 2.65-993.49). Supervision by a metabolic center improved the outcome (18% vs 57% MD; OR, 6.17; 95% CI, 1.15-33.11), whereas migrational background and biochemical phenotype (high versus low excretor status) had no significant effect. Interpretation: Follow-up of neonatally diagnosed patients with GA-I in Germany clearly demonstrates that the inclusion of this rare disease in the NBS disease panel has significantly improved the neurological outcome of affected individuals. The establishment of and adherence to evidence-based treatment recommendations, and supervision by experienced metabolic centers helps to minimize the number of patients who do not benefit from NBS. Ann Neurol 2010;68:743-752
First published: 29 October 2010
Gesehen am 26.04.2023